Kepuasan Konsumen dan Positif Ewom di Tiktok Shop: Menguji Peran Pengakuan Sosial dan Pengalaman Emosional - Saiful, Saiful; Santoso, Bejo; Maulidani, Yurdi; Romadloni, Mohammad; Hakim, Reza Luqman (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This study aims to analyse the influence of customer satisfaction on the decision to engage in positive electronic word of mouth (eWOM) on TikTok Shop, while considering the moderating role of emotional experience and social recognition. The research method employed is Partial Least Squares–Structural Equation Modelling (PLS-SEM), based on a survey of 100 TikTok Shop users who had made at least two purchases and previously provided reviews. This approach was chosen because it enables testing of complex relationships between latent variables in consumer behaviour studies. The findings indicate that customer satisfaction alone does not exert a significant effect on the decision to post positive reviews on TikTok Shop. However, when moderated by emotional experience, the relationship between satisfaction and the decision to provide positive reviews becomes significant. This shows that consumers are more motivated to share favourable experiences when they feel emotionally connected to the purchasing process. By contrast, social recognition does not enhance the link between satisfaction and the decision to engage in positive eWOM, suggesting that the desire for acknowledgement from others is not always a decisive factor. These results highlight the importance of emotional factors in shaping consumer behaviour within social commerce platforms. While satisfaction provides a rational basis for evaluation, emotions act as a key driver that converts satisfaction into active sharing behaviour. Theoretically, this study expands the understanding of eWOM dynamics in the context of video-based social commerce. Practically, the findings emphasise the need for businesses to design strategies that not only ensure customer satisfaction but also create emotionally engaging experiences capable of stimulating deeper consumer involvement and voluntary advocacy.